1985
DOI: 10.1113/jphysiol.1985.sp015902
|View full text |Cite
|
Sign up to set email alerts
|

Static and dynamic responses of carotid sinus baroreceptors in dogs with chronic volume overload.

Abstract: SUMMARY1. In this study we determined if there are any alterations in carotid sinus baroreceptor discharge in a model of heart failure in the dog.2. The left carotid sinus was isolated and perfused at 100 mmHg with a modified Krebs-Henseleit solution. Two groups of dogs were used: a normal group and a group with a chronic aorto-caval fistula (a.v.f.) of up to 20 weeks duration.3. The a.v.f. group had a significantly elevated heart rate and left ventricular end diastolic pressure as well as an increased arteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

1987
1987
2000
2000

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…Although most previous studies have examined baroreceptor sensitiviy in congestive heart failure in the dog, [14][15][16] we assessed this issue in rabbits with AR, the animal model in which we previously described alterations in hemodynamics and -adrenergic receptors over the 4 weeks after left ventriocular overloading. 17 Myosin heavy chain isoenzyme composition, which has a central role in the pathophysiology of congestive heart failure, is similar in rabbits and humans.…”
Section: Baroreceptor Sensitivity In Congestive Heart Failurementioning
confidence: 99%
See 4 more Smart Citations
“…Although most previous studies have examined baroreceptor sensitiviy in congestive heart failure in the dog, [14][15][16] we assessed this issue in rabbits with AR, the animal model in which we previously described alterations in hemodynamics and -adrenergic receptors over the 4 weeks after left ventriocular overloading. 17 Myosin heavy chain isoenzyme composition, which has a central role in the pathophysiology of congestive heart failure, is similar in rabbits and humans.…”
Section: Baroreceptor Sensitivity In Congestive Heart Failurementioning
confidence: 99%
“…Niebauer and Zucker showed that baroreceptor gain was lower in dogs with chronic volume overload induced by aortocaval fistula than in control dogs for both the step and lowest ramp rate pressure changes. 15 A steady-state method may have an advantage in assessing both vagal and sympathetic traffics whereas a ramp method essentially reflects vagal traffic. 33 Although several previous animal studies were undertaken in the anesthetized state, 6,15,16 we assessed baroreceptor-mediated reflex in the awake state to minicompared with that before production of AR (1.78±0.47 msec/mmHg).…”
Section: Assessment Of Baroreflex Sensitivitymentioning
confidence: 99%
See 3 more Smart Citations